Glucomannan from Porang (Amorphophallus muelleri) Improves Short-Chain Fatty Acid in Wistar Rat with High-Fat and High-Fructose Diet - Harimawan, Agustinus I Wayan (Babali Publisher, 2024)
Introduction: Short-chain fatty acids (SCFAs) improve lipid profile and prevent coronary artery disease. Searching for nutrition based on local foods that might raise the body's SCFA levels is imperative. Porang (Amorphophallus muelleri) is a plant with a high concentration of glucomannan that is investigated to have a healthy benefit. This study aimed to investigate the effect of glucomannan from Porang (A.muelleri) on SCFA in Wistar rats with a high-fat, high-fructose diet.Methods: This was an experimental study with a randomized and post-test-only control group design. Thirty male Wistar rats were divided into five groups: a normal control group, a negative control group given a high-fat, high-fructose diet, and treatment groups given Porang glucomannan 25mg, 50mg, or 100mg/200gBW. Twenty-eight days after the intervention, the SCFA level was measured using gas chromatography–masstry (GC/MS). Data were analyzed in SPSS.Results: The treatment group with Porang glucomannan 50 mg/200gBW has the highest mean SCFA level (3.98±0.83 nmol/ml) compared to normal control (1.56±0.24), negative control (2.18±0.45), treatment group 25mg/200gBW (1.81±0.26), and treatment group 100mg/200gBW (2.58±0.38). Kruskal Wallis test showed significant differences among groups (p<0.001). Post hoc test revealed that SCFA in the treatment group 50 mg was significantly higher than the normal control and negative control group.Conclusion: Glucomannan from Porang (A.muelleri) at 50 mg/200gBW doses improves short-chain fatty acid in Wistar rats with high-fat and high-fructose diets.